Destruction analysis of the antifoam additive - Кузнєцова, Олена Яківна (Technology audit and production reserves, 2015)
The article presents the results of a study changes in the structural-group composition of molecules of the antifoam additives, which occur during long-term use of hydraulic oil "Gіdranykoil FH-51", thereby reducing the guaranteed resource life of oil and, in turn, the reliability of the hydraulic system of the aircraft and the aircraft safety factor. The types of structural molecules of polyorganosiloxane liquid, their group composition and atomic mass are defined. It is found that during long-term use of hydraulic oil antifoam additive molecule susceptible to degradation breaking Si–O linkages and internal molecular rearrangement. As a result, these processes are formed low-molecular structure capable of sealing, thermal degradation, and participation in the processes of oxidation of hydrocarbons of all types.